Analisa Sistem Administrasi Pergudangan Pada Departemen Warehouse PT. Transkon Jaya Tbk Kota Balikpapan - Yizrel Junus Kende; Alisa Alaina; Nur Kemala Dewi (Lembaga Pengembangan Kinerja Dosen, 2023)
In companies, office administration systems have an important role, especially warehousing administration in the warehouse section that handles inventory. Warehousing administration in the warehouse department is the spearhead of all records of incoming and outgoing goods. PT. Transkon Jaya has a warehouse section that handles spare parts inventory for vehicles or equipment that is rented, the inaccuracy of data in recording administration at the warehouse will have an impact on the company's operations. Based on the description above, the authors conducted a study entitled Analysis of Warehouse Administration Systems at the Warehouse Department at PT Transkon Jaya Tbk, Balikpapan City. The research method used in this research is Descriptive Qualitative Research which uses comparative analysis techniques through literature study, observation, and interviews. From the results of research and analysis, it can be concluded that the warehousing administration system in the Warehouse Department at PT. Transkon Jaya Tbk Balikpapan uses 2 (two) mechanisms, namely a computerized mechanism that uses the MYOB application and a manual mechanism. However, the application used is an accounting computer application, not an application specifically for inventory administration, which can provide information regarding the location of goods, the number of goods, the date of goods coming in, the date of goods left, and the amount of stock in the warehouse in real-time.